Integrasi Vertikal Pasar Produsen Gabah dengan Pasar Konsumen Beras di Provinsi Lampung - Nazilah, Nazilah; Noer, Irmayani; Kurniawan, Henry (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Rice is a food ingredient that is a top priority in government food policy.  Rice prices in Indonesia experienced an increase in the first quarter of 2024, rice prices jumped 21.3% compared to last year. The difference in rice prices occurs because of the weak agribusiness structure and market mechanisms that occur in Indonesia.  Market integration analysis can be carried out through several measurements, namely price correlation, price transmission, and Vector Error Correction Model (VECM) analysis. This research aims to analyze the relationship between rice prices at the farmer level, grain producers and consumers in Lampung Province, as well as analyzing the integration of the rice market at the farmer level, grain producers and rice consumers in Lampung Province. The data used is secondary data in the form of time series data, namely data on grain prices at the producer or farmer level and retail rice prices at the consumer level in Lampung Province from 2018 to 2023. The data analysis method uses price correlation analysis and the Vector Error Correction Model (VECM ) using Eviews.10 software. The research results show that the price of rice at both market levels, namely between the grain producer market and the rice consumer market in Lampung Province, is positively correlated.  Based on the results of the market integration analysis, it shows that the rice market in Lampung Province has not been fully integrated in the short term, while the results of the cointegration test show that in the long term the market at the grain producer and retailer level in Lampung Province is well integrated, so it can be concluded that the rice market in the Province In the short term, Lampung has not been well integrated, while in the long term the rice market in Lampung Province is integrated.